1988
DOI: 10.1177/088506668800300403
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Reviews : Rapid Tranquilization of the Agitated Intensive Care Unit Patient

Abstract: Agitation in intensive care unit patients is a problem that is often ignored or undertreated. The presence of agita tion warrants a thorough investigation for underlying causes (e.g., metabolic and systemic abnormalities, drug intoxication or withdrawal, hypoxia, and pain) so that the precipitating disturbances can be identified and cor rected. When these conservative measures fail to con trol a patient's agitation, it may be necessary to resort to mechanical restraint and sedating medication. The au thors pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…Большое время полувыведения галоперидола (18-54 часа) обусловлива ет необходимость нагрузочной дозы для достижения быстрого ответа. Начальная доза 2 мг, с последующим повторным введе нием доз (в 2 раза больших) каждые 15-20 минут [54]. Высокие дозы (более 400 мкг/день) могут использоваться, но вызывают удлинение интервала QT и высокий риск экстрапирамидных расстройств.…”
Section: лечение делирияunclassified
“…Большое время полувыведения галоперидола (18-54 часа) обусловлива ет необходимость нагрузочной дозы для достижения быстрого ответа. Начальная доза 2 мг, с последующим повторным введе нием доз (в 2 раза больших) каждые 15-20 минут [54]. Высокие дозы (более 400 мкг/день) могут использоваться, но вызывают удлинение интервала QT и высокий риск экстрапирамидных расстройств.…”
Section: лечение делирияunclassified
“…Tesar and colleagues published 2 articles reporting use of high-dose haloperidol resulting in rapid tranquilization in patients with hyperactive manifestations of delirium in a critical care setting. 10,11 Treatment was initiated at 5 to 10 mg of intravenous or intramuscular haloperidol depending on severity of agitation. The dose of haloperidol was subsequently doubled every 20 minutes until the patient was stabilized.…”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 99%
“…This utilises the fact that lorazepam's onset of action is faster and allows a lower dose of haloperidol to be used. Tesar et al [7,9] reported the safe use of haloperidol in doses of 100 mg per day or more in agitated patients post cardiac surgery and presents a protocol for its safe use, but the complication of Torsades de pointes is well documented. Hassaballa [2] reported 19 cases of Torsades after haloperidol and Huyse [6] reported a case of cardiac arrest after 7.5 mg of haloperidol.…”
Section: Comment(s)mentioning
confidence: 99%